2015
DOI: 10.3348/kjr.2015.16.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemoembolization Using Gelatin Sponges or Microspheres Plus Lipiodol-Doxorubicin versus Doxorubicin-Loaded Beads for the Treatment of Hepatocellular Carcinoma

Abstract: ObjectiveTo retrospectively compare treatment of hepatocellular carcinoma (HCC) with transarterial chemoembolization (TACE) using gelatin sponges or microspheres plus lipiodol-doxorubicin vs. doxorubicin-loaded drug-eluting beads (DEB).Materials and MethodsA total of 158 patients with HCC received TACE from November 2010 to November 2011 were enrolled in this study, including 64 (40.5%) received TACE with lipiodol-doxorubicin and gelatin sponges (group A), 41 (25.9%) received TACE with lipiodol-doxorubicin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…DEB-TACE has been reported to have a more stable phar-macokinetics profile than C-TACE in both animal and clinical trials. 6,7,16,17 An earlier trial comparing C-TACE and DEB-TACE showed that complications associated with the procedure and the effusion of anticancer drugs and hepatic dysfunction were less likely to occur in the DEB-TACE group. In addition, the objective response rate and disease control rate of HCC were found to be better in the DEB-TACE group.…”
Section: Discussionmentioning
confidence: 99%
“…DEB-TACE has been reported to have a more stable phar-macokinetics profile than C-TACE in both animal and clinical trials. 6,7,16,17 An earlier trial comparing C-TACE and DEB-TACE showed that complications associated with the procedure and the effusion of anticancer drugs and hepatic dysfunction were less likely to occur in the DEB-TACE group. In addition, the objective response rate and disease control rate of HCC were found to be better in the DEB-TACE group.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies involving 909 subjects reported the disease control rate (19,21,25,26,30,32,35,36,38). Of those studies, 2 were published by the same group.…”
Section: Comparison Of the Disease Control Ratementioning
confidence: 99%
“…The overall response rate (ORR) was reported in 13 studies (12,17,19,21,25,26,(30)(31)(32)34,35,36,38). Due to the high heterogeneity found among the included studies ( χ 2 = 6.67, d.f.…”
Section: Comparison Of the Objective Response Ratementioning
confidence: 99%
“…Among 16 articles that retrospectively analyzed DEB‐TACE versus cTACE, five described the superiority of DEB‐TACE, three showed an advantage of cTACE, and the remaining eight showed equivalent effect or adverse events. Individual evaluation of objective response rate, TTP, OS, and adverse events, did not show definite advantages of DEB‐TACE over cTACE in these retrospective studies.…”
Section: Transcatheter Arterial Therapymentioning
confidence: 99%